2014
DOI: 10.1007/s10643-014-0644-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toys on the Play Quality of Preschool Children: Influence of Gender, Ethnicity, and Socioeconomic Status

Abstract: This study examined the effects of nine toys on the play of 60 3-and 4-year-old children in culturally diverse preschool classrooms. The toys, which varied in their features and intended uses, were selected from a list of those that were nominated by teachers and parents as being developmentally beneficial. Each toy was video recorded for 240 h during free play time in four different classrooms. Researchers coded 828 two-minute segments of children's play with these toys using a play quality with toys (PQT) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 34 publications
1
50
0
4
Order By: Relevance
“…This socialisation can result in children learning social expectations that are different for both sexes and that are supported by obvious and oblique, intentional and unintentional influences from families, friends, schools and the media(ibid). Further, Trawick-Smith et al (2015) found that gender play differences are evident during free play. Boys and girls, even when playing with the same toys, engage differently with the toys along gender lines and the quality of play appears to promoted different skills.…”
Section: Gender Schemasmentioning
confidence: 96%
“…This socialisation can result in children learning social expectations that are different for both sexes and that are supported by obvious and oblique, intentional and unintentional influences from families, friends, schools and the media(ibid). Further, Trawick-Smith et al (2015) found that gender play differences are evident during free play. Boys and girls, even when playing with the same toys, engage differently with the toys along gender lines and the quality of play appears to promoted different skills.…”
Section: Gender Schemasmentioning
confidence: 96%
“…Çocukların gelişimlerinin değerlendirilebilmesi için bu farklılıkların ne olduğunun, çocukların neden oyun oynadıklarının ve gelişimlerine olan katkısının bilinmesi çok önemlidir. Bu nedenle çocukların akranlarıyla olan iletişim becerileri, sosyal uyumları ve sosyal çatışmaları incelenmelidir (7) . Çocukların oyun sırasındaki davranışları aile ve öğretmen tarafından gözlem yöntemi ile sağlıklı bir şekilde değerlendirilmelidir (8) .…”
Section: Introductionunclassified
“…Research shows that play is one of the best methods for learning in preschool period (Kaytez and Durualp 2014, Pivec 2007, Wu, Hsiao et al, 2012, Pellegrini 1980, Stagnitti, Bailey et al, 2017, Trawick-Smith, et al, 2015.…”
Section: Introductionmentioning
confidence: 99%